Long-Term Risk of Hospitalization Among Five-Year Survivors of Childhood Leukemia in the Nordic Countries - Sørensen, Gitte Vrelits (J Natl Cancer Inst, 2019)
BACKGROUND: Adverse effects from childhood leukemia treatment may persist or present years after cure from cancer. We provide a comprehensive evaluation of subsequent hospitalization in five-year survivors of childhood acute lymphoblastic leukemia (ALL), acute myeloid leukemia (AML), and chronic myeloid leukemia (CML). METHODS: In the Adult Life after Childhood Cancer in Scandinavia Study, we identified 4003 five-year survivors diagnosed with childhood leukemia 1970–2008 in Denmark, Sweden, Iceland, and Finland. Survivors and 129 828 population comparisons were followed for first-time nonpsychiatric hospitalizations for 120 disease categories in the hospital registries. Standardized hospitalization rate ratios and absolute excess rates were calculated. All statistical tests were two-sided. RESULTS: Survivors of ALL (n = 3391), AML (n = 389), and CML (n = 92) had an increased overall hospitalization rate compared with population comparisons. The rate ratio for any hospitalization was 1.95 (95% confidence interval [CI] = 1.83 to 2.07) in ALL, 3.09 (95% CI = 2.53 to 3.65) in AML, and 4.51 (95% CI = 3.03 to 6.00) in CML survivors and remained increased even 20 years from leukemia diagnosis. Corresponding absolute excess rates per 1000 person-years were 28.48 (95% CI = 24.96 to 32.00), 62.75 (95% CI = 46.00 to 79.50), and 105.31 (95% CI = 60.90 to 149.72). CONCLUSION: Leukemia survivors have an increased rate of hospitalization for medical conditions. We provide novel insight into the relative and absolute rate of hospitalization for 120 disease categories in survivors of ALL, AML, and CML, which are likely to be informative for both survivors and healthcare providers.